Pelestarian Budaya Lokal melalui Edukasi Pengenalan Batik Tulis Khas Kabupaten Malang bagi Kelompok PKK - Aris Siswati; Alif Dewantara; Noeke Chrispur Madiarsih (University of Merdeka Malang, 2020)
Batik is one of the original handicrafts of the Indonesian which is very well known for its beautiful motifs and is also full of various philosophical values. Efforts to preserve local culture, especially written batik, must be made in order to strengthen the Indonesian identity. One form of effort made is through education which aims to provide insight into the knowledge of batik. The participation of academics through their obligations to carry out community service becomes a bridge in these conservation. For this reason, the activities are carried out through an educational program on the introduction of batik, especially written batik typical of Malang to the empowerment of family welfare or PKK in Banjararum Village, Singosari, Malang Regency. The activity agreed upon between the service team and the PKK Banjararum was to provide insight into knowledge in the form of socialization to PKK about batik. The result of this activity is the increased awareness of the community about the importance of preserving the Indonesian nation's culture, especially batik which in turn creates awareness to use Indonesian original batik, creating ideas for a productive economic sector for the community by utilizing existing potential and human resources, and the sustainability of efforts to preserve the environment through culture.DOI: https://doi.org/10.26905/abdimas.v5i3.5037